Radicals resistance and protest in Colonial Malaya - Aljunied, Syed Muhd. Khairudin 1976- (Northern Illinois University Press, 2015)
Radicals tells the story of a group of radical Malay men and women from ordinary social backgrounds who chose to oppose foreign rule of their homeland, knowing full well that by embarking on this path of resistance, they would risk imprisonment or death. Their ranks included teachers, journalists, intellectuals, housewives, peasants, preachers, and youths. They formed, led, and contributed to the founding of political parties, grassroots organizations, unions, newspapers, periodicals, and schools that spread their ideas across the country in the aftermath of the Great Depression, when colonialism was at its height and evident in all areas of life in their country. But when their efforts to uproot foreign dominance faltered in the face of the sanctions the state imposed upon them, some of these radicals chose to take up arms, while others engaged in aggressive protests and acts of civil disobedience to uphold their rights. While some died fighting and hundreds were incarcerated, many lived to resist colonialism until their country attained its independence in August 1957, all of these Malay radicals were devoted to becoming free men and women and to claiming their right to be treated as equals in a world riddled with prejudice and contradictions.